2009
DOI: 10.1007/s12257-008-0279-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alum on nitrification during simultaneous phosphorous removal in anoxic/oxic reactor

Abstract: ^Äëíê~Åí= Phosphorus and nitrogen are the important eutrophication nutrients. They are removed in the anoxic/oxic reactor through simultaneous precipitation and biological nitrogen removal. The effect of alum a commonly used simultaneous precipitant on biological nitrification and denitrification are investigated in the present study. Simultaneous removal of phosphorus was carried out using the coagulant alum Al 2 (SO 4 ) 3 ·14H 2 O at 2.2 mol ratio. Before the start of simultaneous precipitation the nitrifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 19 publications
2
1
0
Order By: Relevance
“…In other words, the addition of the external carbon source -1 in Run 1 and 0.7 and 0.9 mg l -1 in Run 2. The present study recorded high phosphorous removal efficiency when compared to other similar systems used to treat domestic wastewater (Rajesh et al 2008;Yu and Zhou 2010). The improvement of phosphorous removal is likely due to the use of UCT-like recirculation which is beneficial for PAO organisms and subsequent phosphorous removal.…”
Section: Sludge Characteristicssupporting
confidence: 54%
See 1 more Smart Citation
“…In other words, the addition of the external carbon source -1 in Run 1 and 0.7 and 0.9 mg l -1 in Run 2. The present study recorded high phosphorous removal efficiency when compared to other similar systems used to treat domestic wastewater (Rajesh et al 2008;Yu and Zhou 2010). The improvement of phosphorous removal is likely due to the use of UCT-like recirculation which is beneficial for PAO organisms and subsequent phosphorous removal.…”
Section: Sludge Characteristicssupporting
confidence: 54%
“…It was basically composed of a mixed carbon source, macronutrients (N and P), an alkalinity control (NaHCO 3 ) and a microelement solution (Rajesh et al 2008 and TP of 5.0 ± 0.1 mg l -1 with pH 6-7. The sludge from aerobic basin was withdrawn at a flow rate of 2 % Q.…”
Section: Methodsmentioning
confidence: 99%
“…Do et al (2013) conducted the study with the main objective to investigate the influence of sludge pretreatment on the nitrification rate and found that the nitrogen removal efficiency reduced from 85 to 74%. Moreover, similar results are also coherent with other authors (Banu et al 2008(Banu et al , 2009.…”
Section: N-mineralization Of Compostsupporting
confidence: 93%